Genome-wide survey of Calcium-Dependent Protein Kinases (CPKs) in five Brassica species and identification of CPKs induced by Plasmodiophora brassicae in B. rapa, B. oleracea, and B. napus - Lu, Junxing; Yang, Nan; Zhu, Yangyi; Chai, Zhongxin; Zhang, Tao; Li, Wei (Frontiers in Plant Science, 2022)
Calcium-dependent protein kinase (CPK) is a class of Ser/Thr protein kinase that exists in plants and some protozoa, possessingCa2+ sensing functions and kinase activity. To better reveal the roles that Brassica CPKs played during plant response to stresses, five Brassica species, namely Brassica rapa (B. rapa), Brassica nigra (B. nigra), Brassica oleracea (B. oleracea), Brassica juncea (B. juncea), and Brassica napus (B. napus) were selected and analyzed. In total, 51 BraCPK, 56 BniCPK, 56 BolCPK, 88 BjuCPK, and 107 BnaCPK genes were identified genome wide. The results showed that a typical CPK gene was constituted by a long exon and tandem short exons. They were unevenly distributed on most chromosomes except chromosome A08 in B. napus and B. rapa, and almost all CPK genes were located on regions of high gene density as non-tandem form. The promoter regions of BraCPKs, BolCPKs, and BnaCPKs possessed at least three types of cis-elements, among which the abscisic acid responsive-related accounted for the largest proportion. In the phylogenetic tree, CPKs were clustered into four primary groups, among which group I contained the most CPK genes while group IV contained the fewest. Some clades, like AT5G23580.1(CPK12) and AT2G31500.1 (CPK24) contained much more gene members than others, indicating a possibility that gene expansion occurred during evolution. In addition, most CPK proteins contained one protein kinase, four EF-hand domains, palmitoylation sites, and generally consisted of 9 to 11 motifs. Furthermore, 4 BraCPKs, 14 BolCPKs, and 31 BnaCPKs involved in the Plasmodiophora brassicae (P. brassica) defense response in resistant (R) or susceptible (S) materials were derived from online databases, leading to the discovery that some R-specific induced CPKs, such as BnaC02g08720D, BnaA03g03800D, and BolC04g018270.2J.m1 might be ideal candidate genes for P. brassica resistant research.